2010
DOI: 10.1212/wnl.0b013e3181dd4423
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to pesticides increases the risk of incident AD

Abstract: Background: Commonly used organophosphate and organochlorine pesticides inhibit acetylcholines-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
169
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(187 citation statements)
references
References 25 publications
9
169
0
4
Order By: Relevance
“…It is also important to note there is a small but growing body of literature to suggest that OP exposure may even represent a potential risk factor for Alzheimer's disease as well as some of the other neurodegenerative disorders mentioned previously (Hancock et al, 2008;Hayden et al, 2010;Zaganas et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note there is a small but growing body of literature to suggest that OP exposure may even represent a potential risk factor for Alzheimer's disease as well as some of the other neurodegenerative disorders mentioned previously (Hancock et al, 2008;Hayden et al, 2010;Zaganas et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several studies have recognized that chronic or occupational pesticide exposure is a possible risk factor for dementia. For example, one of our selected cohort studies 12 reported an increased risk for all-cause dementia among individuals who had been exposed to pesticides (HR = 1.38; 95% CI = 1.09, 1.76). In addition, the Canadian Study of Health and Aging found that exposure to occupational pesticides doubles the risk of vascular dementia 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from in-vitro models and animal studies suggests that long-term/low-dose pesticide exposure may lead to the neuronal loss in specific brain regions, resulting in subsequent cognitive impairment, decreased memory and attention, and loss of motor function 10,11 . These neurobehavioral dysfunctions may ultimately lead to AD and other forms of dementia later in life 12,13 . Pesticides are known neurotoxins.…”
mentioning
confidence: 99%
“…A significant rise in Alzheimers and other forms of dementia through exposure to organochlorine pesticides has been suggested (Hayden et al 2010). A link between thyroid disorders and organochlorine exposure in women in farming communities of Iowa and North Carolina has also been reported (Goldner et al 2010).…”
Section: Long-term Health Effectsmentioning
confidence: 99%